Rancang Bangun Motor Listrik Submersible pada Aplikasi Bow Thruster Kapal - Cuk Supriyadi Ali Nandar; Asep Andi Suryandi; Dewi Rianti Mandasari; Katri Yulianto; Sumardi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
This paper proposes the design of submersible electric motors for vessel's bow thruster. The advantages of the proposed design in comparison with a conventional electric motor are smaller diameter, without gear driven, better efficiency, low noise level, and minimizing oil leakage or more environmentally friendly. The proposed design has been manufactured and will be applied to navigation vessels. Simulation and factory acceptance test (FAT) results show that the proposed design has fulfilled the naval architect requirements and give better performance in comparison with conventional electric motor designed by NEMA standard's frame.